Geocaching w edukacji – przegląd międzynarodowych doświadczeń Część 3. Organizacja zajęć - Referowska-Chodak, Ewa (Leśne Prace Badawcze, 2020)
This article discusses the organization and conduct of educational activities using geocaching. In the scientific literature, the organization of geocaching classes is divided into three main stages: preparation, field work and evaluation. The preparation stage includes issues such as the role of the educator, the scenario itself, the duration of the classes, the length and course of the route, the number and location of caches, the coordinates and type of caches, potential descriptions of caches or the preparation of hints as well as the content of caches, necessary aids and preparing the students. In terms of the implementation of the fieldwork, the following issues need to be addressed: the role of the educator, introduction to classes, division of participants into teams, locating and working with caches as well as a summary of the activities. The evaluation stage should include an evaluation of the participants’ performance, the activities/thematic trails by the participants and the educational effect by the organizers. Additionally, other educational possibilities for using geocaching, such as tasks based on internet geocaching services, the use of existing caches and the establishment of caches by students are also briefly discussed. Due to the universality of the recommendations presented in the literature, educational geocaching can be implemented in every country, including Poland, both in formal and informal education, e.g. in the State Forests, national parks and landscape parks. Although this innovative teaching method involves a lot of initial work, its positive educational and social effects more than compensate for the invested time.